Drugs disorder by design: why Britain's war on drugs targets the poor and protects the privileged - Peatfield, Elizabeth (Palgrave pivot, 2025)
Chapter 1: A Condensed History of British Drug Policy and Legislation 1860 to Present -- Chapter 2: Based on Science -- Chapter 3: The War on Some Drugs, who really pays the price -- Chapter 4: Functional vs Problematic Drug Users in the UK A Policy Blind Spot -- Chapter 5: Who Benefits from the Criminalisation of Drug Users -- Chapter 6: Between Evidence Ethics and Enforcement -- Chapter 7: Legal Highs Loopholes and the Politics of Panic -- Chapter 8: The Real Harm Why Alcohol is the Most Dangerous Drug -- Chapter 9: Beyond Prohibition What a Just Drug policy could look like -- Chapter 10: Conclusion What a Difference it could all Make.